Implementasi Pembelajaran IPS pada Peserta Didik Berkebutuhan Khusus - Firmansyah, Aris; Aisyah Nur Sayidatun Nisa (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to describe the implementation of Social Studies (IPS) learning for students with special needs in Grade IX at SMP Negeri 5 Semarang. The study employed a qualitative approach with a case study design. The research subjects consisted of the principal, Social Studies teacher, guidance and counseling teacher, students with special needs, and their parents. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. Data validity was ensured through source, technique, and time triangulation. The findings revealed that Social Studies learning was implemented inclusively through planning based on the Individualized Education Program (IEP), flexible instruction using personal approaches and various teaching methods and media, and assessments adapted to students' abilities while maintaining the same learning achievement standards. The study concludes that Social Studies learning for students with special needs at SMP Negeri 5 Semarang has been implemented inclusively through adjustments in instruction and assessment according to students' needs. Despite challenges related to the absence of a Special Education Teacher and the diverse conditions of students, collaboration among stakeholders supported the effectiveness of inclusive learning. Keywords: Inclusive Education, Inclusive School, Individualized Education Program (IEP), Social Studies Learning, Students with Special Needs.